5.75+.75x=4.50+1x

Simple and best practice solution for 5.75+.75x=4.50+1x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5.75+.75x=4.50+1x equation:


Simplifying
5.75 + 0.75x = 4.50 + 1x

Solving
5.75 + 0.75x = 4.50 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
5.75 + 0.75x + -1x = 4.50 + 1x + -1x

Combine like terms: 0.75x + -1x = -0.25x
5.75 + -0.25x = 4.50 + 1x + -1x

Combine like terms: 1x + -1x = 0
5.75 + -0.25x = 4.50 + 0
5.75 + -0.25x = 4.50

Add '-5.75' to each side of the equation.
5.75 + -5.75 + -0.25x = 4.50 + -5.75

Combine like terms: 5.75 + -5.75 = 0.00
0.00 + -0.25x = 4.50 + -5.75
-0.25x = 4.50 + -5.75

Combine like terms: 4.50 + -5.75 = -1.25
-0.25x = -1.25

Divide each side by '-0.25'.
x = 5

Simplifying
x = 5

See similar equations:

| -.8x+4=-12 | | 3(b+4)=4(2b-3) | | -15-(15y-1)=2(7y-16)-y | | x^2+10z+24= | | 2+3(y-1)=3(2-y)+5 | | 9f-1=3f+9 | | 2(-8n-8)+3(4n+2)=5+n+3n-7 | | 5.75+.75=4.50+1x | | 6x-8x+5=-2(x+5)+7 | | -.8+4=-12 | | -42*2-7u*2+2u*2= | | -3.7=-37.0 | | 9-5t=64 | | 7-5z=17+5 | | 6x+-3=4x+9 | | 389.77=160+1.11x | | 3x+y=3y-3 | | -(-5x+10)-5x=-10 | | X+x-25+x-25(3)=275 | | 8-3(4-y)=-27 | | 70=16c-8 | | -45x+4=-12 | | 3-2m+7m=5m-3m | | 131-(6x+12)=6(x+9)+x | | 3[b+7]=30 | | 3d-12=9 | | N-25=-25 | | 4x+2=3(x-3)+6 | | -3x-10=-50 | | 2(5-1.7*1.4)=15.1-7*1.4 | | D+4.7=2.8t(12) | | N-35=-18 |

Equations solver categories